How Students View on Instagram in Self-Development in Mastering English Language - Ermawati, Ermawati; Madani; Ahmed Sardi (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study was to characterize the students' perspectives on the Instagram app as a means of enhancing their self-development competence and improving their English language proficiency. Six undergraduate EFL learners who were enrolled in the State Islamic Institute of Palopo, Indonesia's English Language Education Study Program served as study participants. Google forms with open-ended questions were used to gather the students' opinions about using Instagram to independently improve their understanding of the English language. The study's conclusions showed that the students appreciated using Instagram to learn English since it helped them improve their English vocabulary. Additionally, Instagram offered them a abundance of accounts that produce English-language learning materials. Additionally, Instagram helped students focus and comprehend English with ease. Ultimately, Instagram increased the students' motivation to spread knowledge to others. The findings of this study offer English language teachers and lecturers who are attempting to innovate their language teaching pedagogy useful and accessible ways to use Instagram.